Evaluation of physical characteristics of chevon as affected by post-mortem carcass dressing and freezing preservation - E. A. Apata; O. O. Olaleye; O. A. Apata; M. T. Olugbemi; A. B. Omojola (Теория и практика переработки мяса)
This study was conducted to investigate the effects of post-mortem dressing methods and freezing preservation on the physical characteristics of chevon. Twenty-seven Red-Sokoto male goats between 10 and 12 months of age weighing 18–20 kg were purchased, stabilized and slaughtered. The carcasses were randomly allotted to three post-mortem dressing procedures (scalding, skinning and singeing) and meat from thigh cuts was frozen for 0, 7, 14 and 21 days. Meat samples were excised each day after thawing for physical analysis and data collected were subjected to analysis of variance (ANOVA) in a completely randomized design experiment with 3x4 factorial arrangement. The significant means were separated with the Duncan multiple range test at p<0.05. The results showed that the post-mortem dressing methods and freezing affected Red-Sokoto chevon significantly with the singeing method exerting the highest detrimental effects on physical attributes of meat with the exception of color, yield and pH, while the skinning method exerted the least detrimental effects. Also, cold, cooking and drip losses as well as thermal shortening, cold shortening and pH values increased between the 14th and 21st day, while color, yield, water holding capacity, texture and shear force values decreased across the three treatments during freezing periods. The effects were more significant in singed and scalded meat than in skinned chevon. It was recommended, therefore, that skinning method be encouraged if meat from Red-sokoto male goats is to be frozen and the period of freezing be limited to 14 days for wholesome meat.